389 WHEN YOU HAVE A HAMMER, EVERYTHING LOOKS LIKE A NAIL. (15th December 2022) - Alfieri, Michele; Francesca, Coraducci; Brugiatelli, Leonardo; Paolini, Federico; Gianmarco, Bastianoni; Belleggia, Sara; Coretti, Francesca; Torselletti, Lorenzo; Maurizi, Kevin; Stronati, Giulia; Principi, Samuele; Molini, Silvano; et al.
Abstract: Introduction: ST-segment elevation myocardial infarction (STEMI) is one of the most lethal manifestations of ischemic cardiomyopathy. Diagnosis is made through clinical signs, symptoms and, most importantly, the surface ECG. Several conditions mimicking the STEMI repolarization pattern have been hitherto recognised and their identification is of utmost importance in order to provide the correct treatment. Case report: A 81-years old man affected by multiple sclerosis and dysphagia was admitted to our hospital for continuous vomiting. His anamnesis was relevant for an episode of bowel obstruction; ECG upon admission exhibited ST-elevation in D1, aVL, V5 and V6 with specular ST-depression in the inferior leads. The patient was unconscious, therefore making it impossible to report any kind of symptoms, in addition, bedside echocardiography showed a thoracic fluid collection completely obscuring cardiac chambers. Physical examination displayed tachypnoea and, most importantly, a tender abdomen with no bowel movements; this specific finding added to the anamnesis and the echocardiography called into doubt the possibility of a real myocardial infarction. Preliminary laboratory findings pointed out high levels of C-reactive protein, procalcitonin and both indirect and direct bilirubin. Being hesitant about the next step, we took a second look at the only clue we had so far, the ECG. At a deeper analysis, the aspects of repolarization did not exactly resemble the convex ST-elevation seen in STEMI presentations, rather reminding (in D1 and aVL) of a pattern called "spiked helmet sign", described as an index of poor prognosis and increased intrathoracic pressure in critically ill patients. Considered a high suspect of bowel obstruction, a nasogastric tube was placed and, soon after, 3 litres of dark fluid were drained from his stomach. In the following minutes, we witnessed the progressive normalization of the ST alterations initially observed, thus excluding the necessity of a cath lab activation. A CT scan was then performed showing a faecaloma extending from the rectum to the descending colon creating a complete obstruction associated with intestinal pneumatosis and gastric distension. As soon as troponin levels came out normal, the patient underwent surgery, but, unfortunately, he died a few days later due to intervention-related complications. Discussion: Although current literature reports several cases of STEMI phenocopies, with a minority referring to bowel obstruction, this is one of the rarely reported circumstances with no instrumental findings or patient symptoms available to support the diagnosis. As most physicians know, diagnoses are rarely straightforward and instrumental findings, especially in the context of an emergency, may drive to incorrect deductions if not properly analysed or incoherent with the clinical context. The "old-fashioned" anamnesis and clinical evaluation may be the keys to unlocking the true diagnosis in difficult contexts where pitfalls can mislead the clinician to the most obvious and quickest conclusion.